PULMONARY ABSCESS AS A COMPLICATION OF COVID-19 INFECTION - Simić, Vladimir; Radovanović, Jovana (Halo 194 Scientific Journal of Emergency Medicine, 2021)
Introduction/Objective:An abscess is a limited purulent pneumonia with necrosis and colic of lung tissue. Infection with the COVID-19 led to the formation of lung abscesses.Case report:Due to the obvious manifestation of COVID-19,an 81-year-old man,on the advice of a doctor from the ambulance,as examined in a Covid clinic and referred for home treatment,according to the current epidemiological situation.During the night,the symptoms progress in the form of shortness of breath and cough.He was hospitalized for 35 days due to radiographic verification of the band-spotted shadows on both sides and laboratory-confirmed COVID-19. Twenty two days after discharge,the patient was examined at the EC of the CC of Serbia on suspicion of pulmonary embolism due to dyspnea,occasional hemoptysis and rapid fatigue.The finding on multislice computed tomography records an abscess in the basal part of the left lung.Conclusion:Due to lung abscesses,a rare but possible complication of COVID-19,it is necessary to monitor patients after hospitalization.